Identyfikacje pojęcia sprawiedliwości społecznej - Stoiński, Andrzej (Annales. Etyka w Życiu Gospodarczym, 2016)
In the 1840’s due to Luigi Taparelli and Antonio Rosmini emerged the term of“social justice”. From this time, its meaning has developed in many ways. Thepaper brings up some applications of the notion. In the literature of the subject onecan find numerous identities of “social justice”. The article focuses on the identityof this term with justice framed as: legal, distributive, commutative, penal, andrestorative. Some of these concepts assumes and requires existence of some kindof social persons. By briefly analysing those notions the author tries to show thespecificity of particular types of meanings assigned to the social justice.